Celebrating Adam Watkins' Third Birthday at Special Spot - Watkins, Howard::::::::: (1981)
Annie Tilley lighting candle on birthday cake; Adam, Seth Tilley, Marshall Chambers, Clay, ? Devon Bleile-Kratzer; and co-teacher ? At table